2024
DOI: 10.3390/app14051886
|View full text |Cite
|
Sign up to set email alerts
|

The Baking Quality of Wheat Flour (Triticum aestivum L.) Obtained from Wheat Grains Cultivated in Various Farming Systems (Organic vs. Integrated vs. Conventional)

Katarzyna Wysocka,
Grażyna Cacak-Pietrzak,
Beata Feledyn-Szewczyk
et al.

Abstract: The quality of flour is influenced by various factors including genotype, environmental and agronomic conditions, post-harvest grain storage, and milling technology. Currently, the EU focuses on reducing mineral fertilization and promoting less intensive agrotechnology (organic and integrated farming). This research aimed to assess the baking value of flour obtained from four spring wheat cultivars cultivated in three farming systems: organic (ORG), integrated (INT), and conventional (CONV). The wheat grains w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Postponed wheat sowing and later application of N fertilizer have been found to contribute to increased nitrogen content in plants, which has a positive influence on plant yield [38]. An experiment conducted by Wysocka et al [52] showed that differentiated N fertilization, within the whole range of applied doses, caused an increase in the value of technological parameters describing wheat grain. Reducing N fertilization reduces the content of nitrogen in wheat and barley grains [53], an effect that is generally confirmed in this study, especially in the cultivation of spring wheat and spring rape.…”
Section: Discussionmentioning
confidence: 99%
“…Postponed wheat sowing and later application of N fertilizer have been found to contribute to increased nitrogen content in plants, which has a positive influence on plant yield [38]. An experiment conducted by Wysocka et al [52] showed that differentiated N fertilization, within the whole range of applied doses, caused an increase in the value of technological parameters describing wheat grain. Reducing N fertilization reduces the content of nitrogen in wheat and barley grains [53], an effect that is generally confirmed in this study, especially in the cultivation of spring wheat and spring rape.…”
Section: Discussionmentioning
confidence: 99%